PENGETAHUAN SISWI KELAS XI TENTANG DAMPAK ANEMIA TERHADAP KESEHATAN REPRODUKSI - Angelina, Clarita; Siregar, Debi Novita; Siregar, Patimah Sari; Anggeria, Elis (Universitas Prima Indonesia, 2020)
Anemia is a clinical condition of reducing the quality of red blood cells. In circulation that is marked by low hemoglobin levels in the blood. The impact of anemia on iron nutrition results in a pale, weak, tired, dizzy, and decreased concentration of learning. Other causes: the level of knowledge of adolescent girls and the length of menstruation. The purpose of this study was to determine the description of class XI knowledge about the effects of anemia on reproductive health in SMA 6 Medan 2019. This research is descriptive using primary and secondary data. The populations in this study were 30 teenage girls in SMA 6 Medan as many as in-class XI IPA I. The sampling technique of this study was using purposive sampling technique. The sample of this study was 30 students. The results of this study indicate that the majority of people who lack knowledge are 16 people (54%) and the minority of people who have good knowledge is 4 people (13%). The study conclusion is that the majority of female student’s knowledge about the effects of anemia on reproductive health is lacking. For the school and adolescents, it is hoped that they will increase their knowledge by came and working with health workers to promote health about the effect of anemia on reproductive health.